The association of severely worn dentition resulting from betel nut chewing with temporomandibular disorders: a cross-sectional study - Yundong Liu; Tao Yin; Mi He; Changyun Fang; Shifang Peng (BMC, 2023)
Abstract Background Most studies support parafunctions play an important role in temporomandibular disorders (TMD), whereas the association between tooth wear and TMD remains controversial. Betel nut chewing as a parafunction is popular in South and Southeast Asia. We therefore investigated the association of severely worn dentition resulting from betel nut chewing with TMD. Methods A cross-sectional analysis of 408 control participants (male: 380, female: 28, 43.62 ± 9.54 years) and 408 participants with betel nut chewing related severely worn dentition (male: 380, female: 28, 43.73 ± 8.93 years) who received dental and TMD checkup according to Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) in Health Management Center, Xiangya Hospital was performed. Betel nut chewing related severely worn dentition meant all the natural teeth had moderate to severe tooth wear [Tooth Wear Index (TWI) ≥ 2)] including ≥ 2 severe wear teeth (TWI ≥ 3) due to betel nut chewing. Multivariable logistic regression analysis was used. Results After adjusting for age, gender, betel nut chewing related severely worn dentition, oral submucosal fibrosis, number of missing teeth, number of dental quadrants with missing teeth, visible third molar and orthodontic history, variables of age, gender and betel nut chewing related severely worn dentition were significant for overall TMD. Multivariable analysis showed betel nut chewing related severely worn dentition was significantly associated with intra-articular TMD [odds ratio and 95% confidence intervals: 1.689 (1.271-2.244), P = 0.001] in a betel nut chewing dose-dependent manner. Conclusion Betel nut chewing related severely worn dentition was associated with intra-articular TMD.